Competition and distress in banks in India: An application of panel data - Jagjeevan Kanoujiya; Shailesh Rastogi; Venkata Mrudula Bhimavarapu (Cogent Economics & Finance, 2022)
Financial distress (FD) is a crucial issue that needs to be resolved in time; otherwise, it may adversely influence society's areas. Therefore, identifying the factors responsible for FD and how these factors affect FD is an exciting area of research. Given this, this paper proposes investigating the effect of competition on the bank's FD in India. This paper uses the data of 34 banks operating in India for the observation period (2016-2019). Three variants of Altman's Z-score are used for the assessment of FD. Lerner's index of the banks is developed for the competition measurement. A panel data analysis is further performed for regression analysis. The current study has an interesting outcome. The findings reveal that high market power or low competition lowers financial distress and adds more financial stability in banks in India. This paper provides fresh evidence on the connection between market power and FD of banks in India. Moreover, no other study has been observed to use all the three variants of Altman's z-score to provide robustness and reliability in results. Therefore, the study has a significant contribution and a novelty in its approach.
Keywords: 330; competition; market power; financial distress; Bankruptcy; Lerner's index